Foreign body reaction to soft tissue filler simulating atypical lipomatous tumor: Report of a case - Singh Naorem; Kahvic Mirza; Rifaat Amre; Alenezi Ibrahim (Wolters Kluwer Medknow Publications, 2010)
Injectable silicone or microimplant has been extensively used for the soft tissue augmentation. Here we report a case of cystic granulomatous reaction to injectable tissue filler, possibly liquid silicone, used for tissue augmentation in the buttocks. Patient presented with a progressive painful swelling in the lower back over L4-L5 and S1 lumbosacral region of 4-month duration. The lump was excised and microscopic examination revealed multiple cystic spaces of variable size lined by foreign body giant cells and macrophages. There were proliferating spindle cells admixed with many multivacuolated mononuclear cells simulating lipoblasts. These morphologic features were highly reminiscent of atypical lipomatous tumor. To our knowledge, this is the second recorded case from the Middle East of such an unusual foreign body reaction. The dermatologists and pathologists should be aware of this unsual lesion. Although rare, this reaction can have important esthetic implication and the patient should be informed about their risk.